Pengaruh Pendidikan Tinggi terhadap Tantangan Dunia Kerja - Adlini, Miza Nina; Pasaribu, Putri Apriani; Adisti, Yuda; Ritonga, Eka Wahyu Putri M.; Holila, Nur; Nasution, Rusdiah Murni (EduInovasi: Journal of Basic Educational Studies, 2024)
This research is about higher education and the challenges of the world of work. The research method used is qualitative with a literal study with qualitative data collection by finding and compiling data obtained from several sources or systematically arranged research. From the observations that have been obtained that it takes the cooperation of various parties. Skills or skills are still being developed so that after graduation they have no difficulty in finding work rather than just relying on the cognitive (knowledge) aspect. Keywords: Higher Education, Job Challenges, Unemployment